CULTIVATION OF SAMPLES OF VEGETATIVELY PROPAGATING VEGETABLE CROPS IN COLLECTION AREAS - Aliyarov Muhiddin Absamatovich; Niyazova Dilnoza Khudaiberganovna; Toshmetova Komila Nigmatovna; Toshmetova Komila Nigmatovna; Kurbanbekova Fatima Tokhmapulatovna (Journals Park Publishing, 2022)
The article presents the results of the research carried out in order to update and restore the fertility of the collection samples of sweet potato (Ipomoea batatas), Jerusalem artichoke (Helianthus tuberosus) and garlic onion (Allium sativum) belonging to vegetatively reproducing vegetable crops stored in the gene pool.
Keywords: genetic resources, gene pool, crop samples, vegetative organs, population.